Charisma and canon : essays on the religious history of the Indian subcontinent - Dalmia, Vasudha, 1947-; Malinar, Angelika; Christof, Martin (New Delhi ; New York : Oxford University Press, 2001)
Papers presented at a symposium held at Blaubeuren, Germany from May 17-21, 1997.
Includes bibliographical references.
Keywords: India -- Religion -- Congresses